KEPUASAN KERJA KADER POSYANDU SEKELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Rezki Rahmawati M; Jasfar Jas; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research it is based on the state of satisfaction work posyandu cadres seen from factors motivation. Because factors the motivation is characteristic the base that must be is used to development satisfaction work posyandu cadres Sekelurahan Simpang Tiga Kecamatan Bukit Raya Kota Pekanbaru. Formulation problems research is whether the internal factors cause satisfaction work posyandu cadres Sekelurahan Simpang Tiga Kecamatan Bukit Raya Kota Pekanbaru? . The purpose of this research is to find the internal factors cause satisfaction work posyandu cadres Sekelurahan Simpang Tiga Kecamatan Bukit Raya Kota Pekanbaru. Population in this study 85 cadres posyandu. So research sample areas 46 people and 20 people sample test on critical level 10 %, sample used is simple random sampling. An instrument data collection that is chief with 45 a statement and if the trial live 43 a statement valid for in made instrument research. Data analysis through descriptive analysis quantitative. The research findings against two these indicators can be concluded that the two indicators can be said is considerably higher. The internal factor considered to be high because of the responsibility of self posyandu cadres is the factor that raises the satisfaction of working. While external factors considered to be high because of administration policy and that is in posyandu make posyandu cadres feel satisfied with his work.Key words: Satisfaction Work, Satisfaction Work Posyandu Cadres